Influence of the crystallization on the molecular mobility and ionic DC conductivity behaviors of relaxor ferroelectric P(VDF‐TrFE‐CTFE) terpolymers. Issue 16 (26th April 2016) - Liu, Qing; Yin, Xunqian; Richard, Claude; Capsal, Jean‐Fabien
ABSTRACT: The dynamics of semicrystalline poly(vinylidene fluoride‐trifluoroethylene‐chlorotrifluoroethylene) (P(VDF‐TrFE‐CTFE)) terpolymers were fully investigated as a function of temperature and frequency, by means of broadband dielectric spectroscopy. Four types of relaxation regimes were observed over the full dielectric spectroscopy, namely β (second) relaxation in the sub‐glass state, α (segmental dynamics) in the rubbery state, the Curie transition and space charge carrier motion at high temperatures. Constrained segmental dynamics were observed in the terpolymer containing the highest crystalline fraction for which a narrow relaxation time distribution was found. These results indicate a decreasing average size of the cooperative rearranging region over the crystalline fraction. A decrease of the strength index values also implied a more fragile behavior for terpolymers with a higher degree of crystallinity. An exceptional increase in dielectric strength Δ ε α was found as the crystallinity increased. This behavior could be explained by an enhanced interphase (constrained amorphous phase). The Curie transition showed an accelerating relaxation rate for a more fragile terpolymer. Moreover, a motion of the space charge carrier ions was observed in the higher temperature range. Finally, there was evidence that the segmental dynamics in the amorphous phase was responsible for the motion of the space charge carrier ions. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1645–1657 Abstract : The molecular mobility associated with segmental dynamics ( α relaxation) and local motion ( β relaxation) of semicrystalline polymers strongly depends upon crystallinity and morphology. In this work, α relaxation and β relaxation processes in the amorphous phase as a function of the evolution of crystallization were investigated by broadband dielectric spectroscopy. Due to the enhancement of the interphase region, the terpolymer with a higher crystallinity fraction exhibited fragile behavior. The ferroelectric‐paraelectric Curie transition and charge carrier motions were also addressed.